Developing Reading Strategies to Enhance Vocabulary Comprehension and Purposeful Reading among Third-Grade Elementary Students - Zai, Irene Netalis Mawati; Zendrato, Citra Kasih; Giawa , Ester Linda Putri; Harefa , Erlin Harta Yanti; Ziliwu, Yurman; Zendroto, Junita Putri Ningsih; Laia, Agustina; Waruwu, Yaredi (Yayasan Pendidikan Bima Berilmu, 2026)
English reading instruction in elementary schools often emphasizes mechanical decoding and pronunciation accuracy, while reading comprehension and reading purposes receive limited attention. This condition leads third-grade students to experience difficulties in understanding texts due to limited vocabulary knowledge and unclear reading objectives. This study aimed to develop English reading strategies that emphasize vocabulary comprehension and purposeful reading for third-grade elementary school students. The study employed a Research and Development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. A needs analysis was conducted through classroom observations and teacher interviews to identify students’ reading difficulties. The results indicated that students’ limited vocabulary knowledge caused them to read English texts mechanically without clear reading purposes. Based on these findings, an English reading strategy module was developed with a structured instructional syntax consisting of setting explicit reading objectives, introducing vocabulary contextually, guided reading practice, comprehension checking, and gradual scaffolding toward independent reading. Expert validation results confirmed that the developed module was valid, practical, and appropriate for classroom use. A limited try-out also showed positive teacher responses and increased student engagement during reading activities. In conclusion, the developed English reading strategies effectively support vocabulary development and purposeful reading in elementary school English instruction.